The Description Of The Knowledge Of Pregnant Women About The Initiation Of Early Breastfeeding - Irmawati; Andi Suswani (Jurnal Life Birth, 2017)
Early breastfeeding initiation is the process of letting a baby suckle itself immediately after birth. This is the nature and grace of God that has been prepared for us. Doing it is also not difficult, it only takes about one to two hours. Early initiation of breastfeeding or abbreviated as IMD is a program that is being intensively recommended by the government. Breastfeeding and not breastfeeding is an illustration that IMD is not a mother's breastfeeding program but babies who must actively find their own nipples. The purpose of this writing is a known description of the knowledge of pregnant women about the initiation of early breastfeeding (IMD) in Borong Rappoa Health Center, Kindang District, Bulukumba Regency. The results of the study are presented in the form of a presentation frequency table, where each table displays the number of pregnant women classified by age, education, and occupation, then the knowledge of pregnant women is categorized as good, sufficient, and lacking. The type of research used is a simple descriptive method with a sample size research as many as 34 pregnant women With the sampling technique in this study is the total sampling that is all pregnant women who come for a pregnancy check-up at Borong Rappoa Health Center, Kindang District, Bulukumba Regency amounted to 34 people. Based on the results of the study of respondents who were well knowledge by 3 respondents (8.8%), the number of respondents who were knowledgeable was 17 respondents (50.0%), and respondents who were knowledgeable were 14 respondents (41.2%). In conclusion, the knowledge of pregnant women about the initiation of early breastfeeding (IMD) in the Borong Rappoa Puskesmas, Kindang Sub-district, Bulukumba Regency is mostly in the category of Enough, as many as 17 respondents (50.0%).